VIDEOGAMES AS MEANS OF INCREASING STUDENTS’ MOTIVATION - Horban, Olexandr; Maletska, Maria (The Modern Higher Education Review, 2020)
The article is devoted to the use of videogames in order to increase students’ motivation and influence on educational process. Motivation is of particular interest to re-searchers because of its importance to learning and work with students. Several types of motivation apart from motivation for achieving: the motivation for power, the need for affiliation, the need to know (curiosity), the need for approval. Main components of the learning motivation are described. It is stated that videogames are complex phenomenon the main characteristics of which are apparatus for playing, interactivity and rules of playing game. Two ways of use of videogames in educational process are described: gamification and game-based learning. Typical elements of gamification which increase students’ motivation are defined. It is concluded that videogames have significant impact on emotional state of students, encourage them to participate in learning, improve social interaction and decrease anxiety and fear of failure. The use of videogames in educational process can solve the problems with lack of motivation during the work in class.